Edad de poda en las características agronómicas y el rendimiento en Allium fistulosum L. cebolla china, Loreto. 2023 - Mori Sangama, Jessy Mercedes (2024)
The objective of this research was to evaluate the effect of leaf pruning age on the agronomic characteristics and yield of *Allium fistulosum* (Chinese onion) under the conditions of the Loreto region. Four treatments were implemented: no pruning, pruning at 60 days, pruning at 90 days, and pruning at 60 and 120 days. The harvest was carried out at 180 days for all treatments. The methodology used was a completely randomized block design with 5 replications. The variables evaluated included plant height, plant width, number of bulbs per plant, and total plant weight. The results showed no statistically significant differences between the pruning treatments for any of the variables. The highest plant height was observed in the 60 and 120 days pruning treatment, with an average of 49.62 cm, while the highest plant width was 7.21 cm in the no pruning treatment. The highest number of bulbs per plant was recorded in the 60-day pruning treatment, with 23.24 bulbs per plant, and the highest total plant weight was found in the 60 and 120 days pruning treatment, with an average of 210.12 g per plant. Despite these numerical differences, the results indicate that they are not statistically significant (p>0.05), so it cannot be concluded that one pruning treatment is superior to another. It is concluded that the age and frequency of pruning do not significantly influence the vegetative characteristics or the yield of Chinese onion. The results suggest that leaf pruning can be performed without negatively affecting the plant's productivity.